Pengaruh Komite Audit, Konservatisme Akuntansi, dan Profitabilitas Terhadap Kualitas Audit - Syafira Setianah Putri; Martini Martini (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This study aims to determine the influence of the Audit Committee, Accounting Conservatism, and Profitability on Audit Quality. The sample selection technique in this study uses purposive sampling and was obtained from 48 Food and Beverage companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data analysis used in this study is logistic regression analysis using SPSS version 26 software. Based on the results of the study, it can be concluded that the Audit Committee has a negative and significant effect on Audit Quality, while Accounting Conservatism and Profitability have no effect on Audit Quality.